2022
DOI: 10.3390/vaccines10081187
|View full text |Cite
|
Sign up to set email alerts
|

HPV-Vaccine Hesitancy in Colombia: A Mixed-Methods Study

Abstract: In Colombia, the uptake rate of the HPV vaccine dropped from 96.7% after its introduction in 2013 to 9% in 2020. To identify the behavioural components of HPV-vaccine hesitancy in females aged 15 and under and their families, we conducted a convergent mixed-methods study in which 196 parents/caregivers responded to an online questionnaire and 10 focus groups were held with 13 of these parents/caregivers, and 50 age-eligible girls. The study is novel as it is the first to explore the factors influencing HPV-vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 53 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…Efforts to improve public trust and understanding of the program have since facilitated a rebound, with first-dose rates rising to 39.4% by 2021. Vaccine hesitancy has been linked to insufficient awareness, safety doubts, and connections made between HPV and sexuality [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Efforts to improve public trust and understanding of the program have since facilitated a rebound, with first-dose rates rising to 39.4% by 2021. Vaccine hesitancy has been linked to insufficient awareness, safety doubts, and connections made between HPV and sexuality [39].…”
Section: Discussionmentioning
confidence: 99%
“…HPV encompasses more than 200 viral types, where those known as high-risk (HR-HPV) are the leading cause of neoplastic lesion development. HPV-16 and − 18 are the most significant, followed by 33,35,39,45,51,52,56,58,59, and 68 [2,3]; however, type-specific frequencies vary according to the population type and geographical region analyzed [4]. Additionally, cancer development is multifactorial, influenced by various risk factors associated with sexual behavior and genetic, cultural, and social characteristics of the studied communities [5], and intrinsic characteristics of the viruses present in the infections [6].…”
Section: Introductionmentioning
confidence: 99%
“…Vaccine hesitancy is compromising the progress made against COVID-19 pandemic and the resultant low vaccination uptake indicates a profound social weakness in a country. Furthermore, a recent body of evidence suggested that even healthcare workers were also sceptic and hesitant to receive a jab during COVID-19 pandemic [5] .…”
Section: Vaccine Hesitancymentioning
confidence: 99%
“…For instance, the COM-B framework predicted COVID-19 vaccine acceptability in a study of healthy adults in Iran [ 34 ]. This framework has also been applied to understand and explore behavioral predictors of vaccine hesitancy in terms of HPV, MMR (measles-mumps-rubella), and influenza [ 35 37 ]. As such, the current study applied the COM-B model to identify barriers and facilitators of vaccination uptake to inform future evidence-based interventions aimed at increasing vaccination uptake among PWUD.…”
Section: Introductionmentioning
confidence: 99%